2023
DOI: 10.3389/fmed.2023.1102733
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of prognostic value of preoperative neutrophil-to-lymphocyte ratio for postoperative mortality and morbidity

Abstract: BackgroundThe preoperative elevated neutrophil-to-lymphocyte ratio (NLR) was reported to be associated with poorer outcomes after cancer and cardiovascular surgeries. It is unclear, however, if the predictive value is particular or if it may be applied to other types of surgery. We aimed to assess the prognostic value of preoperative NLR levels for morbidity and mortality after various surgery and determine an optimal threshold for NLR.MethodsWe conducted a cohort analysis on patients receiving surgery at Sich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Because high NLR might reflect an activated immune system and increased systemic inflammatory response, which contributes to worse outcomes by increasing intraoperative cytokines releasing harmful oxygen-derived free radicals with the addition of surgical stress (25)(26)(27). The fact that the VAS Scores found in the study were higher in patients with high NLR also supports this hypothesis.…”
Section: Discussionsupporting
confidence: 57%
“…Because high NLR might reflect an activated immune system and increased systemic inflammatory response, which contributes to worse outcomes by increasing intraoperative cytokines releasing harmful oxygen-derived free radicals with the addition of surgical stress (25)(26)(27). The fact that the VAS Scores found in the study were higher in patients with high NLR also supports this hypothesis.…”
Section: Discussionsupporting
confidence: 57%
“…Previous studies evaluated the prognostic value of NLR in hospitalized patients, mostly in speci c diseases or conditions (22)(23)(24). While a substantial agreement has been reached on the association between high NLR and poor outcomes, a high heterogeneity of the proposed cutoffs has been highlighted (22,(25)(26)(27). In our population, we observed a relatively high mean NLR of 9.5, which could be related to pre-existing comorbidities, most of which are accompanied by the chronic low-grade proin ammatory status that characterizes age-related diseases (28).…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this study are consistent with previous research that has shown that inflammation is a significant risk factor for prolonged LOS in patients undergoing orthopedic surgery. 37 Inflammation can lead to a number of complications such as infection, sepsis, and organ failure, all of which can contribute to a longer LOS. In line with our findings, we also observed that the median LOHS was significantly higher in patients with SII value ≥ 799.86 compared to those with lower SII value (<799.86).…”
Section: Discussionmentioning
confidence: 99%